Spanish national identity, colonial power, and the portrayal of Muslims and Jews during the Rif War (1909-27) - Bolorinos Allard, Elisabeth, 1986- (Colección Támesis. Monografías ;, 2021)
How were Moroccan Muslim and Jewish cultures depicted in Spanish literature, journalism, and photography during the Rif War (1909-27) and what did this portrayal reveal about conflicting visions of Spanish identity?